2011
DOI: 10.1007/s11629-011-2064-0
|View full text |Cite
|
Sign up to set email alerts
|

Digital terrain modelling using Corona and ALOS PRISM data to investigate the distal part of Imja Glacier, Khumbu Himal, Nepal

Abstract: This study used Corona KH-4A and Advanced Land Observing Satellite (ALOS) PRISM images to generate digital terrain models (DTMs) of the distal part of Imja Glacier, where a few supra-glacial ponds (~0.07 km 2 ) expanded into the large Imja Glacier Lake (Imja Tsho, ~0.91 km 2 ) between 1964 and 2006. DTMs and subsequently derived topographical maps with contour intervals of 1 m were created from the high-resolution images (Corona in 1964 and ALOS in 2006) in the Leica Photogrammetric Suite (LPS) platform. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 23 publications
3
62
1
Order By: Relevance
“…6 by assuming that the lake surface has not changed since 2002. This assumption is reasonable as various studies have shown that the level of the lake has not changed significantly since 2002 (Sakai et al, 2007;Lamsal et al, 2011;Fujita et al, 2009).…”
Section: Bathymetric Surveymentioning
confidence: 80%
See 2 more Smart Citations
“…6 by assuming that the lake surface has not changed since 2002. This assumption is reasonable as various studies have shown that the level of the lake has not changed significantly since 2002 (Sakai et al, 2007;Lamsal et al, 2011;Fujita et al, 2009).…”
Section: Bathymetric Surveymentioning
confidence: 80%
“…A number of authors have discussed the details of Imja Tsho's development (Quincey et al, 2007;Bajracharya et al, 2007;Yamada, 1998;Watanabe et al, 2009;Ives et al, 2010;Lamsal et al, 2011). Imja Tsho is bounded to the east by the Imja-Lhotse Shar glacier, to the north and south by lateral moraines, and to the west by the moraine of the former glacier terminus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high-resolution DEM used in this study was generated by Lamsal et al (2011) from Advanced Land Observing Satellite (ALOS) Pranchromatic Remote-sensing Instrument for Stereo Mapping (PRISM) images. The generated DEM has a horizontal resolution of 5 m and relative error of ± 4 m. In order to coregister the DEM with the panchromatic band from the Landsat7 imagery, a shaded version of the DEM was generated using the Hillshade tool in ArcGIS 10.3.…”
Section: Remotely Sensed Datamentioning
confidence: 99%
“…Methods for quantifying glacial lake bathymetry include the interpolation of spot depths calculated from manual 'plumb line' surveys (Yamada and Sharma, 1993;Fujita et al, 2009) or GPS-integrated SONAR (Lamsal et al, 2011;Sawagaki et al, 2012). Such methods are appropriate for the survey of extant glacial lakes, but quantification of the bathymetry of drained lakes necessitated an alternative approach.…”
Section: Moraine-dammed Lake Reconstructionmentioning
confidence: 99%